Environmental and social consequences of the increase in the demand for 'superfoods' world‐wide. Issue 2 (29th April 2020) - Magrach, Ainhoa; Sanz, María José
Abstract: The search for healthy diets has led to a surge in the demand for functional foods or 'superfoods', which have now become popular among the middle‐ and high‐income fractions of the society in developed regions of the world. 'Superfoods' are predominantly consumed far from their centres of origin and out of their cultural context with different environmental and social effects. Here, we present a series of case studies to provide an overview of the different environmental impacts driven by superfood expansion. We show that if these crops are to follow the path of other global commodities, then strong environmental impacts and large carbon footprints are expected in terms of land clearing, use of agrochemicals and transportation during times of high prices (boom) and social problems as farmers have to abandon their livelihoods when prices sink below the cost of production (bust). We also showcase how a combination of management practices, consumer choices and policy changes could help in alleviating the ecological footprint of these crops. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article